2012
DOI: 10.1155/2012/284296
|View full text |Cite
|
Sign up to set email alerts
|

Exponentiated Gamma Distribution: Different Methods of Estimations

Abstract: The exponentiated gamma (EG) distribution and Fisher information matrices for complete, Type I, and Type II censored observations are obtained. Asymptotic variances of the different estimators are derived. Also, we consider different estimators and compare their performance through Monte Carlo simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The numerical results indicated that the method of moments and maximum likelihood provide equivalent results but they recommended maximum likelihood because of its optimal properties. Similar results have been documented in favour of maximum likelihood estimation for Exponential-Pareto distribution [13] and Generalized Pareto-distribution [14].…”
Section: Maximum Likelihood Estimation Is Considered As Most Importansupporting
confidence: 85%
“…The numerical results indicated that the method of moments and maximum likelihood provide equivalent results but they recommended maximum likelihood because of its optimal properties. Similar results have been documented in favour of maximum likelihood estimation for Exponential-Pareto distribution [13] and Generalized Pareto-distribution [14].…”
Section: Maximum Likelihood Estimation Is Considered As Most Importansupporting
confidence: 85%
“…Particular exponentiated G distributions studied in the literature include the exponentiated Frechet distribution (Nadarajah and Kotz 2003), the exponentiated gamma distribution (Nadarajah and Gupta 2007), the exponentiated generalized inverse Weibull distribution (Elbatal and Muhammed 2014), the exponentiated Gumbel distribution (Nadarajah 2006), the exponentiated Lomax distribution (Abdul-Moniem and Abdel-Hameed 2012; Salem 2014), the exponentiated Pareto distribution (Shawky and Abu-Zinadah 2009) and the exponentiated transmuted Weibull distribution (Hady and Ebraheim 2014).…”
Section: Families Of Distributions and R Codementioning
confidence: 99%
“…We write EP to denote the exponentiated Pareto distribution. According to Shawky and Abu-Zinadah (2009) In many lifetime data applications, we can have one unit associated with two or more lifetimes. For the case where we have two lifetimes T 1 and T 2 associated to each unit, we can consider bivariate lifetime distributions such as the studies of Freund (1961), Marshall and Olkin (1967), Mardia (1970), Whitt (1976), Sarhan and Balakrishnan (2007), Kundu et al (2010), Gupta et al (2010), AlMutairi et al (2011), Sankaran et al (2014), and Olkin and Trikalinos (2015).…”
Section: Introductionmentioning
confidence: 99%